Características quantitativas e qualitativas do capim marandú fertilizado com esterco de poedeiras - Mari, Gracielle Caroline (2017)
The objective was to evaluate the dry matter accumulation, the root biomass production, the amount of reserve compounds in the roots and the morphological and chemical composition of the Marandu grass fertilized with laying hen manure in soil with or without scarification at 0, 2 m. The experimental period was from December 20, 2013 to December 21, 2014, and the study was conducted at the Experimental Farm of the State University of Maringá. The experimental design was a randomized block design with four replicates in a 5 x 2 +1 factorial arrangement, with five P doses (0, 25, 50, 100 and 150 kg ha-1) and an additional treatment with chemical fertilization. Soil fertilization and scarification were carried out on December 20, 2013. The dry matter accumulation (AMS) was obtained by subtracting the available MS in the pre-cut of the MS of the residue from the previous cut. Separation of the morphological components of the forage was carried out in green leaf blades (f), stems + green sheaths (cb) and dead material (mm). Afterwards, crude protein (CP), neutral detergent fiber (NDF) and acid detergent fiber (FAD) fractions were analyzed and the lignin content was dissolved in sulfuric acid solution to obtain acid detergent lignin (LDA) ). The fractions f and cb were evaluated for the monomer composition of lignin by oxidation with nitrobenzene. The foliar tissue samples were collected every 90 days. Subsequently, concentrations of magnesium (Mg), calcium (Ca), copper (Cu), manganese (Mn), iron (Fe) and zinc (Zn) were analyzed by atomic absorption spectrometry; Via UV-VIS spectrophotometry for phosphorus (P) and via potassium flame photometer (K). Total nitrogen (N) was quantified by the Kjeldahl method. The samples of the root system were performed once per season, and the weight, total N concentration and non-structural carbohydrates were analyzed. There was no effect for soil management, and the addition of EGP doses of 25 kg of P ha-1, 50 kg of P ha-1, 100 kg of P ha-1, 150 kg of P ha-1 increased 241%, 300%, 361% and 476%, respectively, in relation to the control, and 356% for the chemical treatment. In the morphological composition, the percentage of leaves was higher for the treatments 50 kg of P ha-1, 100 kg of P ha-1, 150 kg of P ha-1 of EGP, being that for the treatments with doses of 50 kg of P ha-1, the chemical was lower than the organic one. The percentage of as + sheath was not influenced by the applied treatments, and the leaf area index was higher in the fertilized plots, mainly for 150 kg P ha-1. For the root system, the treatments decreased the proportions of root biomass. The amount Of reserves, the percentage of total nitrogen and the amount of non - structural carbohydrates, increased with the inclusion of fertilization. The CP of leaf blades and stems were increased with the use of fertilization, mainly in the EGP dose (150). The concentrations of NDF and decreased with the use of chicken manure. Leaf ligin presented only effect for the summer season, and stem lignin presented the highest values in the most fertilized plots. Total nitrogen had the highest mean values for EGP (100) and EGP (150). Phosphorus levels increased in relation to the control, mainly in the EPP (50), EGP (100) and EGP (150) doses. The potassium had its concentrations high by fertilization, especially in the autumn and winter seasons. Iron had no effect on the seasons of summer, autumn and winter, and interaction between treatments in the spring season. Manganese had only effect in the summer, with the highest concentrations at the EGP dose (150). Zinc concentrations showed interaction in the spring season, with the highest concentrations at the EGP dose (150). For the DIVcb, in the seasons of summer, autumn and spring occurred effect for fertilization. For the DIVf, there was effect for fertilization in the seasons of summer, fall and spring, and interaction between winter treatments. The monomer Gf, Sf and Hf showed changes in their concentrations when fertilized. The S: G ratio of the leaf fraction (Sf: Gf) had an effect on fertilization in the summer and autumn seasons. In winter there was a quadratic and positive effect until the treatment of EGP (150) and presented the highest averages for the treatment without incorporation to the soil. The monomer Gcb, Scb and Hcb were influenced by fertilization. For RSc: Gc, only isolated effect for fertilization was observed. The summer had lower values in the EGP (150), and the higher values for EGP (25) and NPK (50); (25), EGP (50) and EGP (150). For winter, the EGP (0) was the treatment with the lowest values in comparison to the others, and in the spring , The highest S: G ratios were observed in the EGP (25) and EGP (150) treatments. A significant and low correlation was observed between the amount of Gf and DIVMSf, and for Gc and DIVMSc for the EGP treatment (50). The NPK treatment (50) showed a positive and significant correlation for the concentration of Sc .